1999
DOI: 10.1161/01.cir.99.2.224
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Formation of 8-Iso-Prostaglandin F and Platelet Activation in Diabetes Mellitus

Abstract: We conclude that DM is associated with increased formation of F2-isoprostanes, as a correlate of impaired glycemic control and enhanced lipid peroxidation. This may provide an important biochemical link between impaired glycemic control and persistent platelet activation. These results provide a rationale for dose-finding studies of antioxidant treatment in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
226
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 670 publications
(250 citation statements)
references
References 27 publications
23
226
1
Order By: Relevance
“…In accordance with previously reported studies, our results confirm that patients with type 1 diabetes have higher levels of oxidative stress than healthy controls matched for age and sex [15,23,27,28].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with previously reported studies, our results confirm that patients with type 1 diabetes have higher levels of oxidative stress than healthy controls matched for age and sex [15,23,27,28].…”
Section: Discussionsupporting
confidence: 93%
“…The intra-individual day-to-day variation of the above-mentioned variables was calculated using a paired samples t test or Wilcoxon's signed rank test, depending on the distribution of the data. Oxidative stress was [15,23], sex [24], age [25] and smoking [17,18,26], all variables that have been reported to be involved in the activation of oxidative stress. For lipid values and blood pressure, we also evaluated the association with urinary excretion of 15 S ð Þ-8-iso-PGF 2α in a univariate model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models allow for flexibility, testing for treatment effects as well as examining for period (time) and order effects (ie, testing for carry over effects), and adjusting for important baseline and time-dependent (ie serum cholesterol levels) covariates. Recently published manuscripts (Reilly et al, 1998;Palombo et al, 1999;Davi et al, 1997Davi et al, , 1999 demonstrated that serum cholesterol affects isoprostane levels, and previous research has suggested that blood tocopherol concentrations may be influenced by serum cholesterol levels. The alcohol treatments in this study significantly altered serum total cholesterol levels (Baer et al, 2002); therefore for vitamin E and isoprostane samples, we used a residual method to adjust concentration for the total serum cholesterol measurement obtained at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…This group demonstrated that F 2 -isoprostanes were superior to other biomarkers used as indices of lipid peroxidation in vivo, including malondialdeyde (MDA) (Longmire et al, 1994). Levels of F 2 -isoprostanes in body fluids are elevated by conditions that are thought to be associated with free radical-induced oxidative stress, including smoking (Morrow et al, 1995;Reilly et al, 1996), hypercholesterolemia (Davi et al, 1997;Reilly et al, 1998;Palombo et al, 1999), diabetes (Davi et al, 1999), and acute and chronic alcoholic liver disease Meagher et al, 1999). Recent research suggests a role for oxidative stress in breast cancer (Kumar et al, 1991;Thangaraju et al, 1994;Li et al, 1999;Novak & Woodcroft, 2000;Ray et al, 2000).…”
Section: Introductionmentioning
confidence: 99%